Akibat setitik kejahatan, rusak kebaikan sebelanga - El Hafiz, Subhan (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2013)
Purpose of this research was to assess how ones make moral judgment in moral dilemma situation if both aspect, receive and reject, were equal. This research was conduct by two studies and the purpose of irst study is to identify evil and good behavior with their own reason. Meanwhile the purpose of second study was to evaluate how ones judge dilemma that create from irst study, which are made of good action with evil reason and evil action with good reason. Method used in irst study was survey to 32 research participants and method for second study was experiment to 53 participants. The irst study was resulting eight evil behavior and six good behaviors that most mentioned by participants with 12 most common reason on each group. Result for second study was ones judge situations of dilemma moral as evil. These results showed that good cannot be combined with evil in one dilemma and it will be judged as evil whatever the order. Based on these indings, ones moral will judge dilemma as evil ifboth side, good and evil, in equal position.